Avaliação e surdez: um olhar dos professores de matemática de alunos surdos - Corrêa, Wallace Cayke Ribeiro (2018)
The present investigation, of a qualitative nature, is a case study that seeks to investigate how the evaluative processes of deaf students in mathematics are being thought and carried out in the view of the regent teachers, taking into account the visual aspects of deafness. Thus, we aim to investigate and analyze the evaluative processes of learning of deaf students, in math, in the view of teachers, therefore, it is necessary to investigate the visual aspects of deafness, based on the assumption that they are part of a set of characteristics that make the deaf subjects have a historically constructed identity and also to elucidate the evaluation methods applied to deaf students in mathematics classes emphasizing their potentialities and weaknesses. To do so, we study the deafness and its main characteristics, as well as a study on the historicity of deaf education involving legislation and public policies and on sign language. We investigate the evaluation in general terms discussing history, conceptions, functions and some of the different types/modalities of evaluation that can be used. In this sense, we emphasize the evaluation from a perspective of inclusion. The data obtained are through interviews with teachers of mathematics of deaf students of the state regular education network, in order to show the vision of these teachers on the subject in question. The interviews were carried out with the teachers in the school where they teach after a previous conversation with the respective coordinators and the acceptance of the teachers in contributing to this research. From the analysis and interpretation of the data through content analysis, we arrive at the categories that involve the social aspects and the pedagogical aspects in relation to the evaluation of the deaf students. We hope, therefore, to contribute to improving the quality of teaching of deaf students by considering the formative capacity that involves the quality of evaluation and to provide a reflective thought about the inclusion of deaf people in the school environment.